Modeling of prediction system : an application of the nearest neighbor approach to chaotic data - Abdul Hamid Nor Zila, Md.Noorani Mohd Salmi (N/A, 2013)
Modeling of prediction system : an application of the nearest neighbor approach to chaotic data by Abdul Hamid Nor Zila, Md.Noorani Mohd Salmi,